2022
DOI: 10.3390/nano12173024
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Cationic Peptide-Coated PHA Nanosphere as an Efficient Vector for Multiple-Drug Delivery

Abstract: Amphiphilic core–shell (ACS) nanoparticles are gaining increasing research interest for multi-drug delivery in cancer therapy. In this work, a new cationic peptide-coated PHA nanosphere was prepared by self-assembly of a hydrophobic core of biodegradable poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) and a hydrophilic shell of fusion proteins of PHA granule-associated protein (PhaP) and cationic peptide RALA through a strong hydrophobic effect. The hydrophobic drug curcumin (Cur) was encapsulated in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The researchers successfully carried CRISPR/Cas9 plasmids to target cells and started gene editing in a mouse model using PHA nanoparticles. In addition to being studied as a delivery method for CRISPR-Cas systems, PHAs are also being investigated as a scaffold material for those systems ( Zhang et al, 2022 ). In a different study, scientists demonstrated how to use a scaffold made of PHA and CRISPR/Cas9 plasmids to treat bone defects.…”
Section: Need For Biomaterials: Advantages Over Other Delivery Methodsmentioning
confidence: 99%
“…The researchers successfully carried CRISPR/Cas9 plasmids to target cells and started gene editing in a mouse model using PHA nanoparticles. In addition to being studied as a delivery method for CRISPR-Cas systems, PHAs are also being investigated as a scaffold material for those systems ( Zhang et al, 2022 ). In a different study, scientists demonstrated how to use a scaffold made of PHA and CRISPR/Cas9 plasmids to treat bone defects.…”
Section: Need For Biomaterials: Advantages Over Other Delivery Methodsmentioning
confidence: 99%
“…This Special Issue, focused on polymeric nanomaterials, reports the latest advances in the synthesis, properties, and applications of this useful and versatile class of nanocomposites. These compounds can be used in drug delivery for the treatment of cancer cells, providing a platform for the co-delivery of nucleic acids and hydrophobic drugs [1]. Another area where such nanopolymers can fruitfully be applied is bone regeneration for maxillofacial reconstructive surgery; new nanomaterials based on hydroxyapatite and poly-l-lactide acid have been shown to be able to recover critical defects in rat mandibles [2], paving the way to their use in humans.…”
mentioning
confidence: 99%